2008
DOI: 10.1212/01.wnl.0000324602.97205.ab
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Erythrocyte Entrapped Thymidine Phosphorylase Therapy for Mngie

Abstract: at SWETS SUB SERVICE on September 23, 2008 www.neurology.org Downloaded fromAt the time of reporting there were no reports of significant hepatotoxicity involving levetiracetam in clinical trials. There has been one reported case of a fatal fulminant hepatic failure in a patient with refractory epilepsy treated with combination carbamazepine and levetiracetam. Autopsy findings revealed complete hepatocyte necrosis 5 but it was unclear if levetiracetam was the only or primary culprit in causality. 5 In our p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 7 publications
0
64
0
2
Order By: Relevance
“…All therapeutic strategies have been aimed at normalizing the accumulation of the toxic metabolites dThd and dUrd in patients. 7,13,14 The observation that platelet transfusions transiently reduced the levels of dThd and dUrd in MNGIE patients, 18 suggested that HSCT from healthy donors could provide a permanent source of TP at levels, producing a significant clinical benefit. Patients undergoing a successful allogeneic HSCT show permanent restoration of TP activity with correction of biochemical abnormalities and progressive improvements in clinical parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All therapeutic strategies have been aimed at normalizing the accumulation of the toxic metabolites dThd and dUrd in patients. 7,13,14 The observation that platelet transfusions transiently reduced the levels of dThd and dUrd in MNGIE patients, 18 suggested that HSCT from healthy donors could provide a permanent source of TP at levels, producing a significant clinical benefit. Patients undergoing a successful allogeneic HSCT show permanent restoration of TP activity with correction of biochemical abnormalities and progressive improvements in clinical parameters.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Therapeutic approaches have so far focused on reducing the systemic overload of these nucleosides. 7,[11][12][13][14] In recent years, several MNGIE patients have been treated with allogeneic hematopoietic stem cell transplantation (HSCT). 4,12,15,16 After successful HSCT, donorderived nucleated blood cells and platelets provided enough TP activity to reduce the dThd and dUrd concentrations to undetectable or nearly undetectable levels, and subsequent slowing of disease progression or mild clinical improvement.…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, a predetermined volume of the patient's blood is removed and subjected to reversible hypo-osmotic dialysis to enable encapsulation of TP within the erythrocytes, which are then returned to the patient. 5,6 EE-TP has the pharmacologic advantages of prolonging the circulatory half-life of TP and minimizing immunogenic reactions.…”
mentioning
confidence: 99%
“…Nowadays, promising new therapeutic options, such as allogeneic haematopoietic stem cell transplantation (HSCT) 28 and CEETP therapy are available 29 . This implies that the diagnosis should be made as early as possible to prevent organ damage and to maximize the benefits of treatments [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%